Simulação do efeito de palhada e adubação nitrogenada na produtividade de cana-de-açúcar - Costa, Leandro Garcia da (2012)
The increasing demand for alternative energy sources for replacing fossil fuels has attracted investments for Brazilian sugarcane industry, which has been widely reconized as a model of renewable energy producer. To ensure financial security is necessary that production of sugarcane provide the socioeconomic and agri-enviromental needs, with emphasis on the relationship between the production of electricity from the burning of biomass and ethanol by new ways of obtaining such as cellulose hydrolysis and the maintenance of sugarcane trash under the soil. Process based crop models based, such as APSIM (Agricultural Productions Systems Simulator), are useful tools for planing the production system and to identify the bottlenecks influencing the profitability of the sector. The objective was to model the growth and productivity of green and burnt sugarcane harvesting systems, under several nitrogen fertilizer levels (60, 120 and 180 kg ha-1). The study was based on two experiments located in Piracicaba-SP and Salinas-MG caried on with cultivar SP80-1842. The evaluation of the model showed that the APSIM-Sugarcane is able to drescribe adequately the growth and productivity of cane sugar production in these environments, once the modeling eficiency (E) was greater than 0.9 for stlak dry mass (MS). Simulations also showed that the amount of trash on the soil would affect the crop yield and the remotion of trash for using in the mills would ultimately decrease the sugarcane yield along the time. However, in these simulations, the crop did not respond to nitrogen fertilization.